2021
DOI: 10.1177/27325016211015405
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency and Characteristics of Facial Injury Following COVID-19 Social Distancing Laws: Newcastle, (Australia) Observations

Abstract: The imposition of COVID-19 social distancing laws serendipitously decreased the frequency and altered the characteristics of facial injury presentation. The purpose of this study was to determine whether the devolution of social distancing laws had the opposite effect. Materials and methods: The authors undertook a retrospective study of the clinical records of a cohort of patients who sustained a facial injury during COVID-19 social distancing devolution. The primary predictor valuable was the 8 week devoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The last of the 4 studies was undertaken by Qiu and Hoffman. 21 They investigated 2020 lockdown / post-lockdown periods. The 8-week figure for 2019 (control) was n = 103, which reduced to n = 73 (30% reduction) for the 2020 lockdown and then rose to n = 120 (64% increase) in the post lockdown period.…”
Section: Discussionmentioning
confidence: 99%
“…The last of the 4 studies was undertaken by Qiu and Hoffman. 21 They investigated 2020 lockdown / post-lockdown periods. The 8-week figure for 2019 (control) was n = 103, which reduced to n = 73 (30% reduction) for the 2020 lockdown and then rose to n = 120 (64% increase) in the post lockdown period.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] In this current study we have shown that the rapid changes in incidence and characteristics of maxillofacial trauma that were observed during the 8 weeks of COVID-19 lockdown have not been mirrored by an equally rapid return to seasonal baseline with the dissolution of major lockdown legislation as was seen in the previously published Australian cohort. 2 In actual fact, the UK has displayed persistent deviations from baseline incidence and patterns despite a 110% increase in maxillofacial trauma admissions between the periods during and post strict COVID-19 lockdown. This increase, although still below baseline, suggests a slow but apparent move toward normality.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] A review of the literature on maxillofacial trauma revealed a total of 9 studies conducted across 6 countries during the peak of COVID-19. [2][3][4][5][6][7][8][9][10] These studies are summarized in Table 3. The 6 studies that included data from previous years (to establish seasonal baseline) found a significant reduction in the incidence of maxillofacial trauma of between 26% and 72.5%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations